Self-Esteem and Social Support are Needed to Increase the Resilience of Student's Mothers - Choiril Anwar; Nikmah Rochmawati; Dewi Khurun Aini (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Resilience is essential for mothers who experience pressure and stress while accompanying their children to take part in distance learning during the COVID-19 pandemic. This study aims to empirically examine the effect of self-esteem and social support on mothers’ resilience of Early Childhood Education students during distance learning assistance. This quantitative study uses a sample of 117 mothers of Early Childhood Education students in Bulusari Village, Sayung District, Demak Regency. The sampling technique used is non-probability sampling with a convenience sampling method. The measuring instrument of this study consisted of a self-esteem scale, a social support scale, and a resilience scale with data collection techniques through questionnaires. The data analysis method in this study used multiple linear regression analysis. The study’s results showed that self-esteem and social support simultaneously significantly affected resilience with a significance value of 0.000 0.05 with a contribution of 41.3%. It proves that self-esteem and social support empirically have a role in the resilience of mothers of Early Childhood Education students during distance learning assistance.